Analisis Kemampuan Pemecahan Masalah Matematis Siswa Kelas X pada Materi Barisan dan Deret Geometri Berdasarkan Teori Polya - Fatrisia, Shella Debora; Tanujaya, Benidiktus; Irnandi, Irfan; Mumu, Jeinne; Istia, Maryo Sopater (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to analyze the influence of the mathematical problem-solving abilities of 10th-grade students at Advent High School in Manokwari on the topic of geometric sequences and series based on Polya’s theory. The method used was a mixed-methods approach with a sample of 30 students. Data were collected through written tests and interviews. The results showed that students’ problem-solving skills fell into the high category (20%), the moderate category (53.33%), and the low category (26.67%). The best regression model obtained was Ŷ = -32.914 + 35.797X₁ + 75.199X₂ - 60.017X₄ + ε, with a coefficient of determination of 46.9%. In conclusion, the ability to understand problems and formulate solution plans are the factors that most influence students’ success in solving geometric sequences and series problems; therefore, mathematics instruction needs to place greater emphasis on developing students’ ability to understand problems, design solution strategies, and think systematically.   Keywords: Geometric Sequences and Series, Problem-Solving Skills, Backward Method, Polya’s Theory